Literatur review: Peran selenium pada diare akut anak - Nolitriani Nolitriani; Yusri Dianne Jurnalis; Yorva Sayoeti (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Acute diarrhea is a manifestation of gastrointestinal dysfunction. If it lasts more than 14 days is called persistent diarrhea. Diarrhea is a leading cause of death in infants and children in Indonesia. Acute diarrhea is a gastrointestinal disease that is considered oxidative stress. Selenium is also thought to be involved in the acute diarrhea process because it contains the gastrointestinal glutathione peroxidase (GPx2 / GPx GI) enzyme which is most commonly found in the epithelial mucosa of the gastrointestinal tract. The aim of this review is to study and analyze the role of selenium in the treatment of pediatric acute diarrhea. This study is a literature review with a narrative method that analyzes research related to the role of selenium in the treatment of acute diarrhea. The results of this study indicate that the administration of selenium reduces the duration of diarrhea. The conclusion of this study is selenium functions in the process of healing acute diarrhea